Daily Disposable Contact Lens use in Adolescents and its Short-term Impact on Self-Concept - TOKER, AYŞE EBRU (ELSEVIER, 2021)
Objective: To determine the short-term effect of contact lens (CL) wear on the self-concept of adolescents. Methods: In this open-label trial, first-time CL wearing adolescents were prescribed Delefilcon A (DAILIES TOTAL1,(R) Alcon, USA) daily disposable CL. To determine the self-concept level of the subjects at dispensing and after one month, the Turkish adapted version of the Piers-Harris Children's Self-Concept Scale (PHCSCS) was used. The subject-reported outcomes included lens wettability, vision quality, comfort, and overall satisfaction. Self-concept was evaluated under six categories. Results: The mean age of the 21 subjects was 16.5 +/- 1.5 years. All subjects had normal biomicroscopic assessments and best corrected visual acuity was 20/20. The mean spherical equivalent was -2.90 +/- 1.18 (range,-4.75 to -1.75). Spectacle use was causing dissatisfaction with their appearance in 90% of subjects (n = 19), the others defined it as uncomfortable. Most subjects had acquired information about CLs from their peers and friends (57%, n = 12). Most of the subscales in the PHCSCS showed increased but statistically insignificant scores after one month. The mean overall satisfaction was 95%. Conclusion: Prescription of CLs may be a good option in adolescents even if the self-concept did not show significant improvement in the short term.
Keywords: daily disposable contact lenses; adolescents; self-concept; Piers-Harris Self-concept Scale; DEPRESSIVE SYMPTOMS; WEAR; PERCEPTION